Pengaruh Pembiayaan Murahabah dan Musyarakah terhadap Return on Assets Bank Umum Syariah - Mardianto, Dedi (Universitas Negeri Surabaya, 2022)
This study aims to analyze the effect of musyarakah and murabaha contract financing on return on assets at Islamic Commercial Banks in Indonesia for the period 2015 to 2019. This research data was taken from access to the official website of OJK (Financial Services Authority) monthly reports on Islamic banking statistics for the period 2015 month. January to December 2019 month. The approach method uses the ECM (Error Correction Model) model. The results obtained on the variable of Musyarakah contract financing have a significant and significant effect on return on assets in long-term conditions. Meanwhile, in short-term conditions, it does not have a significant and significant effect on return on assets at Islamic Commercial Banks in Indonesia for the period 2015 to 2019. In the variable murabahah financing in long-term or short-term conditions, it does not affect return on assets at Islamic Commercial Banks in Indonesia. 2015 to 2019. This could happen because the interest offered by commercial banks is lower than the margin level provided by Islamic commercial banks, so many people choose to take financing from commercial banks.